2005
DOI: 10.1016/s1015-9584(09)60253-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Controlled Trial Comparing Plasmakinetic Vaporesection and Conventional Transurethral Resection of the Prostate

Abstract: PKVP achieved comparable results to traditional TURP and was an effective and safe procedure. However, it did not demonstrate obvious advantages over TURP in this acute regional hospital regular TURP list setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…Yang et al 9 found a significant advantage with the bipolar method, but no significant difference for bleeding tendency was shown in recent studies or in our patients. 10,23 An increased risk of stricture after bipolar resection 20,21 was not confirmed by our findings, which is in accordance with other authors. 8,10,14 The higher number of strictures in the 'bipolar' study arm of some authors 10 might be because of the TUR in saline system.…”
Section: Discussionsupporting
confidence: 87%
“…Yang et al 9 found a significant advantage with the bipolar method, but no significant difference for bleeding tendency was shown in recent studies or in our patients. 10,23 An increased risk of stricture after bipolar resection 20,21 was not confirmed by our findings, which is in accordance with other authors. 8,10,14 The higher number of strictures in the 'bipolar' study arm of some authors 10 might be because of the TUR in saline system.…”
Section: Discussionsupporting
confidence: 87%
“…We saw only a small decrease in hemoglobin in both groups, with no significant difference between the groups. No blood transfusions were given to any patients, and as reported by other authors, no differences in perioperative hemoglobin changes were seen [9,13,14,15,17,18,19,20,21,22]. …”
Section: Discussionmentioning
confidence: 78%
“…We found two trials that also reported longer operating times with the bipolar system [9,24]. Most trials, however, found no difference [13,16,21,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Point estimates and measures of variability were presented in 88% of the studies, although in three studies it was unclear whether means or medians were used as the point estimate measure. 134,152,153 The dropout rate was unlikely to cause bias in 12 studies 124,138,150,[154][155][156][157][158][159][160][161][162] but this information was unclear in 74 (85%) of the studies. Only 16 studies (18%) stated that an intention to treat analysis was performed; however, this seems questionable in 11 of these studies 57,70,125,130,136,139,145,154,[163][164][165] as they failed to include the total number of participants in each arm in the subsequent follow-up assessments and an additional study stated that patients failing to complete the treatment or failing to return for follow-up were substituted.…”
Section: Study Qualitymentioning
confidence: 99%